PERBANDINGAN KUALITAS PELAYANAN INSTALASI FARMASI PASIEN BPJS RAWAT JALAN RUMAH SAKIT PEMERINTAH DAN SWASTA KOTA SEMARANG - Risha Fillah Fithria; Umi Solikhawati (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2015)
7 ABSTRACT Currently there are many complaints against service quality of BPJS patients in pharmacy some hospitals. This study aimed to compare the service quality of BPJS outpatient pharmacy installation at government and and public private hospital Semarang in terms of five dimensions of SERVQUAL. This study was an analytic survey research with cross sectional study design. Sample was BPJS outpatient or patient's family who took the drug in one of the government hospital Semarang  (Tugurejo Hospital’s pharmacy) and one of the public private hospital Semarang (Sultan Agung Hospital’s pharmacy). The sampling technique used purposive sampling method, and used questionnaires to collect data. Expectations and performance scores had been analized used gap analysis and  Mann-Whitney test to compare the service quality of BPJS outpatient pharmacy installation at government and and public private hospital Semarang in terms of five dimensions of SERVQUAL The service quality that terms of five dimensions of SERVQUAL in both of two hospital’s pharmacy installation Semarang could not meet the expectations of BPJS outpatient yet. The biggest gap according to BPJS outpatient in Sultan Agung Hospital’s pharmacy and Tugurejo Hospital’s pharmacy Semarang was the dimension of responsiveness with value respectively -0.73 and -0.63. Dimension that has met the expectations of BPJS  outpatients Sultan Agung Hospital’s pharmacy was tangible dimension with value 0.03. There were significant differences between service quality of  BPJS outpatient pharmacy installation at government  and and public private hospital Semarang above tangible (p. 0,000), and reliability dimension (p. 0,000). Key words : Service quality, Tugurejo Hospital’s pharmacy, Sultan Agung Hospital’s pharmacy, BPJS outpatient, SERVQUAL